Clinical features and risk factors of adenovirus-related plastic bronchitis in children - Yifan Wang; Yuhan Jiang; Ruiwen Xia; Xin Cong; Ning Zhang; Wanyi Li; Xuelin Wang; Ying-Xue Zou (Italian Journal of Pediatrics)
Abstract Background To analyze the clinical characteristics of children with adenoviral pneumonia, identify independent risk factors for early prediction of plastic bronchiolitis (PB), and develop a predictive nomogram. Methods This retrospective study analyzed the clinical data of children diagnosed with adenoviral pneumonia. Patients were categorized into PB and non-PB groups. General characteristics, clinical symptoms, laboratory findings, and imaging results were compared between the two groups. Multivariate logistic regression was used to identify significant risk factors, and a nomogram model was constructed. Results Among the 164 patients, 139 were in the non-PB group and 25 were in the PB group. Multivariate logistic regression identified diminished breath sounds, D-dimer (D-D) levels, and Lactic dehydrogenase (LDH) levels as significant risk factors for PB. The nomogram developed from these factors had an area under the receiver operating characteristic curve (AUC) of 0.904 (95% confidence interval: 0.847–0.960). The Hosmer-Lemeshow test showed good calibration (p = 0.515, X2 = 7.207). Conclusions Diminished breath sounds, D-D levels, and LDH levels are independent risk factors for PB in children with adenoviral pneumonia. The developed nomogram demonstrates high predictive accuracy and good calibration, providing a valuable tool for early prediction and clinical decision-making. Future studies should validate this nomogram in larger and diverse populations.